Thyroid Dysfunction in Pregnancy and its Outcome - Hina Pirzada, Sehrish Ahmad Ali, Asma Qamar Mudassir, Maham Waseem, Humaira Zulfiqar Saifee (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To identify the thyroid dysfunction in pregnancy and its outcomes. Study Design: Prospective study Place and Duration of Study: Department of Obstetrics & Gynaecology, Sheikh Khalifa Bin Zayed Al-Nahyan Hospital/CMH Muzaffarabad Azad Kashmir from 1st October 2021 to 31st March 2022. Methodology: Seventeen hundred pregnant women in third trimester were screened. Out of them, 50 were identified to be suffering from thyroid dysfunction. The pregnant women in their third trimester and within the age group of 18-40 years were recruited. By using enzyme linked sorbent assay the serum levels of TSH, Free T3 and Free T4 were determined for each woman as a routine clinical health check-up practice. The women who had raised analytical levels as well as correlated clinical history were identified as suffering from thyroid dysfunction. These women were further followed for the outcomes of their pregnancy. Results: The prevalence of thyroid dysfunction was 2.9%. There were 42% pregnant women suffering from subclinical hypothyroidism while 36% were having overt hypothyroidism and 12% had subclinical hyperthyroidism. Conclusion: The major outcome of thyroid dysfunction in pregnancy in terms of maternal and fetal outcomes was presence of anemia in women and was 4.89%. In women considering fetal outcomes, low birth weight was observed in 32% neonates with a need of neonatal intensive care for 42% of newborns were seen. Keywords: Thyroid dysfunction, Pregnancy, Outcome